A new numerical model for the analysis on low‐velocity impact damage evolution of carbon fiber reinforced resin composites. Issue 4 (26th September 2016) - Qu, Peng; Sun, Xiaochen; Ping, Lu; Zhang, Dawei; Jia, Yuxi
ABSTRACT: A new numerical simulation method was proposed to predict the mechanical behavior of carbon fiber reinforced resin composites under low‐velocity impact load. The impact damage evolution can be characterized in the form of energy dissipation which can be calculated through the new numerical model. The evolution mechanism of delamination was analyzed through distinguishing between the normal induced delamination and tangential slip induced delamination. The drop weight tests were conducted on composite laminates with five kinds of stacking sequence. Experimental analysis was also presented in this article. The damage area and distribution was investigated through ultrasonic C‐scan. The prediction had a good agreement with the experimental results through the comparison of impact response. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44374. Abstract :